If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(13 + 2d) + -7 = 13 + -1(12 + 2d) (13 * 3 + 2d * 3) + -7 = 13 + -1(12 + 2d) (39 + 6d) + -7 = 13 + -1(12 + 2d) Reorder the terms: 39 + -7 + 6d = 13 + -1(12 + 2d) Combine like terms: 39 + -7 = 32 32 + 6d = 13 + -1(12 + 2d) 32 + 6d = 13 + (12 * -1 + 2d * -1) 32 + 6d = 13 + (-12 + -2d) Combine like terms: 13 + -12 = 1 32 + 6d = 1 + -2d Solving 32 + 6d = 1 + -2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '2d' to each side of the equation. 32 + 6d + 2d = 1 + -2d + 2d Combine like terms: 6d + 2d = 8d 32 + 8d = 1 + -2d + 2d Combine like terms: -2d + 2d = 0 32 + 8d = 1 + 0 32 + 8d = 1 Add '-32' to each side of the equation. 32 + -32 + 8d = 1 + -32 Combine like terms: 32 + -32 = 0 0 + 8d = 1 + -32 8d = 1 + -32 Combine like terms: 1 + -32 = -31 8d = -31 Divide each side by '8'. d = -3.875 Simplifying d = -3.875
| -21=7(y+2) | | 3-4q=10+10q | | X-3+14=5 | | -3.1x=7.75 | | 4z+17=3z+6 | | 8(w-3)=40 | | 8x-(4x+9)= | | 4-5x=-6 | | 4y+4=3y-9 | | (15+x)+(17+x)=72 | | -6a+3=-3(2a-q) | | -32+8+(-22)=-12 | | 7x+4x=68 | | -9y-12=5y+16 | | 2x(54)=7 | | 5(3f+21)=15f+105 | | -9x-4=-10-8x | | 124=6x+7x-6 | | 4x+12=-5x+51 | | 0.45(20)+0.8x=0.7(20+x) | | (x-8)(x^2+4x-12)=0 | | 2x-2(6x-8)=24 | | 1.75x+50=2.50x+39.99 | | 10=-8x+42 | | -8x+22=22 | | 8z-11=1 | | -2x-2-7x=-92 | | 3.3=c/3 | | 8x-7x=-2 | | 15m+23m= | | 28x^5+13x^4-6x^3=0 | | 7a+2a=-14+2a+5a |